(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The factors affecting the dimensional accuracy of 3D scanning using a measuring arm with an integrated scanner and a custom open source 3D printer using FDM technology are researched in this paper, with the purpose of isolating and reducing the sources of errors affecting the results. A consumer 3D printer is analyzed in terms of achieving accurate physical dimensions, consistent shapes, and predictable surface coverage.